(untitled) - Helewitz, Jeffrey (Australia, 2004)
Entertainment Law was written with the reader in mind. Complex legal principles are presented in language that is easily understood and are portrayed using a host of interesting case examples. The edited judicial decisions, showing court interpretation, make this book unlike any other currently on the market.
Keywords: Entertainers,Performing arts; Legal status, laws, etc,Law and legislation; United states,United states